Complexity reduction effects on transient, atomic plasmas. (September 2018) - Abrantes, R.J.E.; Karagozian, A.R.; Bilyeu, D.; Le, H.P.
Highlights: A comparison between various collisional-radiative reduction schemes was conducted. Constant electron or radiation temperatures were used to simulate varying plasmas. Quasi-steady-state and uniform grouping are more rigid in their formulation. Boltzmann grouping is a more flexible and accurate technique for reduction. Abstract: Plasma simulations involving collisional-radiative processes present many computational challenges because of the wide range in scales spanned by the governing set of plasma physics equations. These numerical challenges are primarily caused by limitations in resources such as memory and computational time. Collisional-radiative models deliver a part of the challenge because of the large number of levels and transitions that are associated with atomic plasmas. Multiple complexity reduction techniques have been introduced in the past to overcome this obstacle, including the quasi-steady-state solution, uniform grouping, and the recently-devised Boltzmann grouping. These reduction schemes were tested against full numerical simulations of a simplified, time-dependent argon model, with and without an external Planckian radiation field. Results will show the advantages and disadvantages of using complexity reduction techniques when employed in various plasma regimes.